Firm ownership, FOEs, and POEs - Alice H. Amsden (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
Where the theory of free competition reigns, developing countries should open their arms to investments from all types of enterprises in order to maximize jobs. Ownership, measured by votes of shareholders or boards of directors, is immaterial to performance. Matters change drastically, though, when competition depends on monopolistic assets and market theory no longer rigorously holds. Then, ownership matters. Foreign owned enterprises from developed countries can crowd out privately owned enterprises from developing countries. They can break their back before they have a chance to acquire their own assets. FOEs in direct competition with POEs are not necessary for economic development to flourish, and it is dangerous for a promising POE to confront a privileged FOE in its own back yard, often with the backing of the FOEe's powerful government. In this paper it is argued that because assets differ systematically between FOEs and POEs in their respective stages of evolution, FOEs may not contribute more to economic development in monopolistic industries than POEs. Indeed, the best POEs in the fastest growing emerging economies (e.g. Korea's Samsung, India's Tata, and Brazil's Embraer) tend to be more entrepreneurial than FOEs. The paper discusses the contribution of POEs vis-à-vis FOEs to economic development in emerging economies.
Keywords: L22; L52; L26; 330; entrepreneurship; foreign investment; firm ownership; industrialization